Penerapan Breastcare Untuk Mengatasi Ketidakefektifan ASI Pada Ibu Post Partum Spontan - Nosa Amelinda Windyani; Dewi Erna Marisa; Abdul Rouf; Putri Shintia Devi (Awatara Publisher, 2024)
One of the nursing problems commonly experienced by mothers after post partum is ineffective breastfeeding. Ineffective breastfeeding is a condition where the mother and baby experience dissatisfaction or difficulty in the breastfeeding process. One way to solution this issue is breastcare. This research aims to provide nursing care with a more comprehensive approach covering the entire body system to improve the client's health status. This type of research uses a descriptive method with a case study approach in the form of assessment, data analysis, formulating nursing diagnoses, planning, implementation and evaluation. After 3 days of management of post partum mothers using data collection techniques using interviews, physical examination, observation, and documentation studies, it was found that nursing problems in spontaneous post partum clients, namely acute pain and ineffective breastfeeding, had been resolved. After providing nursing care to the client, complaints of pain decreased and breast milk production increased.